2020
DOI: 10.21203/rs.3.rs-28855/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Point Prevalence survey of antimicrobial use in three hospitals in North-eastern Tanzania

Abstract: Background : Antimicrobial resistance (AMR) is one of the most urgent global health threats with low-resource countries being disproportionately affected. Targeted interventions require insight in antibiotic prescription practices. A point prevalence survey (PPS) is a well-known tool to get insight in antibiotic dispensing practices in hospitals and identify areas for improvement. Here, we describe the results of a PPS performed in a tertiary, regional and district hospital in Kilimanjaro region in Tanzania. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…In low-and middle-income countries (LMIC) such as the nations of sub-Saharan Africa, multidrug-resistant K. pneumoniae, especially strains producing extended-spectrum beta lactamase (ESBL) enzymes present a significant therapeutic challenge. In many countries in sub-Saharan Africa, third-generation cephalosporin (3GC) antimicrobials are the mainstay of management of severe febrile illness [5][6][7], but ESBL production renders these antimicrobials ineffective. For example, in Malawi, a low-income country in South-East Africa, 91 % of K. pneumoniae infections are now resistant to third-generation cephalosporins at one major centre [8]; the BARNARDS study in seven LMIC found K. pneumoniae to be the commonest cause of neonatal sepsis, with all isolates resistant to 3GC [9].…”
Section: Introductionmentioning
confidence: 99%
“…In low-and middle-income countries (LMIC) such as the nations of sub-Saharan Africa, multidrug-resistant K. pneumoniae, especially strains producing extended-spectrum beta lactamase (ESBL) enzymes present a significant therapeutic challenge. In many countries in sub-Saharan Africa, third-generation cephalosporin (3GC) antimicrobials are the mainstay of management of severe febrile illness [5][6][7], but ESBL production renders these antimicrobials ineffective. For example, in Malawi, a low-income country in South-East Africa, 91 % of K. pneumoniae infections are now resistant to third-generation cephalosporins at one major centre [8]; the BARNARDS study in seven LMIC found K. pneumoniae to be the commonest cause of neonatal sepsis, with all isolates resistant to 3GC [9].…”
Section: Introductionmentioning
confidence: 99%
“…The finding of carbapenem resistance conferred by the bla NDM-5 gene in Tanzania is of the great concern, since these isolates also were resistant to virtually all other antibiotics commonly used in Tanzania. Carbapenems have been used as the last alternative for treatment of severe infections caused by multi-drug resistant Gram-negative bacteria infection, the emergence of carbapenem resistance severely limits treatment options for these Lately, the use of carbapenems in Tanzania has been frequent [35], and increased use is anticipated in the future due to increased extended spectrum beta-lactamase (ESBL) producing bacterial infections [36]. Increasing carbapenem use will increase selection for horizontal gene transfer events and, therefore, the movement of the gene and human movement will increase dissemination of carbapenem resistant bacteria around the country.…”
Section: Discussionmentioning
confidence: 99%
“…Em outro estudo conduzido em três hospitais localizados no município de Mosh, no nordeste da Tanzânia a ceftriaxona e o metronidazol foram os antibióticos mais comumente prescritos. (Horumpende et al, 2020). A prevalência do uso da ceftriaxona pode ser justificada por ser um medicamento de amplo espectro que pode ser utilizada na terapia de uma gama de infecções, sendo utilizada como primeira escolha para casos como: meningite bacteriana aguda, pneumonia adquirida pela comunidade, infecções intra-abdominais complicadas, infecções intra-abdominais complicadas, pneumonia hospitalar adquirida; pielonefrite, entre outros (Sonda et al, 2019).…”
Section: Discussionunclassified